PENGEMBANGAN MODUL MATA KULIAH PENGENDALIAN INFEKSI SILANG PADA JURUSAN KEPERAWATAN GIGI - Sukarsih Sukarsih; Saharudin Saharudin; Suratno Suratno (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
The research objectives of this Development to create Learning modules of cross infection controlfor the second semester students in dental nursing Academy Poltekkes Jambi, products that developedmodules contain components based on the study of educational technology in the form of cross-infectioncontrol learning module.The development of cross-infection control module uses the development module of Dick andCarey. The validation toword module which developed by mannen/with; (1) validation of subject contentexpert and validation of instructional design expert; (2) Trial to small group; and (3) Field evaluation. Thesubject of the Try-aur of the research; Consist of nine students for trial to small group and eightteenstudents for praktical-field test. In this research the data were collected by using questionnaires.The validation result of the expert show up excellent category. The Result of trial to small groupand field evaluation, can be cooncludde that the three hundred forty two answers obtained, one hundredforty four respondent answers A (very good) then the module is declared; very valid; our very effective canbe used without repairing and the one hundred ninety eight responden answers B (good) then the moduleis declared; quite validity; our effective enough, to be used but need minor repairing, that is watching fromcomplety aspect, the aspect module component, content exactly aspect, the clear language be used andexciting module. Moduls are presented can be used by students already meets the principlesof preparationmodule according to characteristics such as self-instructional, self contained, standalone, adaptive, user friendly.Form the averall validation results of this study can be concluded that the module of crossinfection control that developed a very visible, then the proposed suggestion in order that the module canbe used by teachers and the students in Dental Nursing Academy Poltekkes Jambi.